Action observation and motor imagery improve motor imagery abilities in patients with Parkinson’s disease – A functional MRI study - Sarasso, Elisabetta; Gardoni, Andrea; Zenere, Lucia; Canu, Elisa; Basaia, Silvia; Pelosin, Elisa; Volontè, Maria Antonietta; Filippi, Massimo; Agosta, Federica (Parkinsonism & related disorders, 2023)
Motor imagery (MI) skills can be affected in Parkinson's disease (PD). We aimed at assessing MI and brain functional changes after action observation and MI training (AOT-MI) associated with gait/balance exercises in PD patients with postural instability and gait disorders (PD-PIGD). Twenty-five PD-PIGD patients were randomized into two groups: DUAL-TASK + AOT-MI group performed 6-week gait/balance training combined with AOT-MI; DUAL-TASK group performed the same exercises without AOT-MI. Before and after training, MI was assessed using Kinesthetic-and-Visual-Imagery Questionnaire (KVIQ) and a MI functional MRI (fMRI) task. During fMRI, subjects were asked to watch first-person perspective videos representing gait/balance tasks and mentally simulate their execution. At baseline patients were compared with 23 healthy controls. PD groups did not differ in the MI scores. Both patient groups increased kinesthetic KVIQ score after training, while only DUAL-TASK + AOT-MI group improved visual and total KVIQ scores. At baseline, both PD groups showed reduced fMRI activity of sensorimotor, temporal and cerebellar areas relative to controls. After training, DUAL-TASK + AOT-MI patients increased activity of anterior cingulate, fronto-temporal and motor cerebellar areas, and reduced the recruitment of cognitive cerebellar regions. DUAL-TASK group showed increased recruitment of occipito-temporal areas and reduced activity of cerebellum crus-I. DUAL-TASK + AOT-MI relative to DUAL-TASK group had increased activity of cerebellum VIII-IX. In DUAL-TASK + AOT-MI group, KVIQ improvement correlated with increased activity of cerebellum IX and anterior cingulate, and with reduced activity of crus-I. AOT-MI improves MI abilities in PD-PIGD patients, promoting the functional plasticity of brain areas involved in MI processes and gait/balance control. •PD-PIGD patients show an altered brain activity during motor imagery (MI).•Motor learning exercises promote functional reorganization of MI-related brain areas.•Brain activity changes correlated with the improvement of MI abilities.